Epidemiological Situation on Tick-Borne Rickettsioses in the Russian Federation in 2010–2019 and Prognosis for 2020 - N. Rudakov V.; S. Shpynov N.; N. Pen`evskaya A.; D. Trankvilevsky V.; E. Yatsmenko V.; A. Blokh I.; Н. Рудаков В.; C. Шпынов Н.; Н. Пеньевская А.; Д. Транквилевский В.; Е. Яцменко В.; А. Блох И. (Journal of Geophysical Research: Biogeosciences, 2020)
Objective of the study was to analyze the incidence of Siberian tick-borne typhus (STBT) in the Russian Federation between 2010 and 2019, Astrakhan spotted fever (ASF) and Mediterranean fever (MF) since official registration, and forecast the development of the epidemic process for endemic rickettsioses for 2020. Materials and methods. The analysis of the incidence of STBT, ASF and MF in the Russian Federation over the period of 2010–2019, 2013–2019 and 2014–2019, respectively, in relation to the results of zoological-entomological monitoring. Results and discussion. The average long-term incidence rate of STBT for 2010–2019 in the Russian Federation on the whole was 1.1 0 /0000 (DI95 1.05÷1.08) without trends towards change. The maximum relative incidence of STBT is typical for the Siberian Federal District (SFD) where the average long-term incidence rate for 2010–2019 amounted to 6.28 per 100 thousand of the population. In the second place is the Far Eastern Federal District (FEFD) – 5.17 0 /0000, in third – the Ural Federal District (UFD) – 0.1 0 /0000. When assessing the 10‑year dynamics of the relative incidence of STBT, we have revealed a significant tendency to increase in the FEFD, a tendency to stabilize in the SFD and a significant downward trend – in the UFD. A reliable increasing trend in STBT incidence was detected in the Altai Republic and in the Khabarovsk Territory. Major decline in STBT incidence was observed in the Trans-Baikal territory, Krasnoyarsk territory, Kurgan Region and the Republic of Khakassia. There is a marked tendency to increase in the incidence of MF in the Republic of Crimea. In the Astrakhan Region and the Republic of Kalmykia, there is an expressed tendency towards the reduction in the ASF morbidity rates. Цель – проанализировать заболеваемость сибирским клещевым тифом (СКТ) в Российской Федерации в период с 2010 по 2019 год, астраханской пятнистой лихорадкой (АПЛ) и средиземноморской лихорадкой (СЛ) с момента официальной регистрации, дать прогноз развития эпидемического процесса при эндемических риккетсиозах на 2020 г. Материалы и методы. Проведен анализ заболеваемости СКТ, АПЛ и СЛ в России за периоды 2010–2019, 2013–2019 и 2014–2019 гг. соответственно в сопоставлении с результатами зоолого-энтомологических наблюдений. Результаты и обсуждение. Среднемноголетний показатель заболеваемости СКТ за 2010–2019 гг. в целом по России составил 1,1 0 /0000 (ДИ95 1,05÷1,08) при отсутствии тенденции к изменению. Максимальная относительная инцидентность СКТ характерна для Сибирского федерального округа (СФО), где среднемноголетний показатель заболеваемости за 2010–2019 гг. составил 6,28 на 100 тыс. населения. На втором месте Дальневосточный федеральный округ (ДФО) – 5,17 0 /0000, на третьем Уральский федеральный округ (УФО) – 0,1 0 /0000. При оценке десятилетней динамики относительной инцидентности СКТ выявлена значимая тенденция к ее повышению в ДФО, стабилизации в СФО и к снижению в УФО. Достоверная тенденция к росту заболеваемости СКТ выявлена в Республике Алтай и Хабаровском крае. Значительный тренд к снижению заболеваемости СКТ отмечен в Забайкальском и Красноярском краях, Курганской области и Республике Хакасия. Выраженная тенденция к повышению заболеваемости средиземноморской лихорадкой выявлена в Республике Крым. В Астраханской области и Республике Калмыкия наметилась выраженная тенденция к снижению заболеваемости астраханской пятнистой лихорадкой.